STUDENTS' PERCEPTIONS AND MOTIVATION FOR LEARNING FOREIGN LANGUAGES - Natalia Hromova (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article is devoted to the evaluation of students' motivation for learning foreign languages dimensions. The analysis of the students' sense of responsibility and readiness to clarify their needs constitutes the novelty of the study. 132 first-year students (21 males and 111 females) participated in the investigation. The research includes a qualitative data analysis of the students' answers based on the grounded theory. The quantitative analysis of the data obtained from the questionnaire adapted from Gardner's Attitudes/Motivation Test Battery defined the students' motivational orientations. The study revealed the growing trend of the students' desire for intellectual development combined with a practical approach to learning foreign languages. The following leading motives for learning languages were defined: "self-development", "opportunities" and "necessity". The students saw self-development as getting acquainted with the culture and broadening their mind to join the international community. Opportunities were associated with career growth and competition. The necessity of learning languages implied moving abroad for a better life or meeting academic demands at university. The findings suggest that modern students want to expand their knowledge, improve communication skills and get integrated into the international community. The analysis also discerned worrying patterns of students' perceptions of learning languages, such as unclear reasons for learning languages and illogical shift of pronouns signifying the students' avoidance of responsibility, the lack of self-confidence and referring to general values accepted in the society. The most important implications for teachers include monitoring their students' perceptions and creating an effective educational environment; raising the students' self-confidence and responsibility.